THE TRANSLATION SHIFTS AND TRANSLATION PROCEDURES OCCURRED IN GARUDA INDONESIA’S MAGAZINE: COLOURS - I Wayan Budiarta; Kasni Ni Wayan; Anak Agung Istri Manik Warmadewi (Center of Language and Cultural Studies, 2022)
This study aimed at identifying and analyzing the types of translation shifts and translation procedures in the Garuda Indonesia: Colors magazine and its translations. The theory used was the theory of translation shift by Catford (1965) and the theory of translation procedures The results showed that in the Colors: Quiet Seoul magazine article, two categories of shifts were come across. Meanwhile, in the Colors: Explore Banyuwangi magazine article there were only Category Shifts found, namely structure shift, class shift, unit shift and intra-system shift. In terms of translation procedures, this research indicated that in the Colors: Quiet Seoul magazine article, there were two translation procedures detected, namely: Adaptation and Borrowing. Meanwhile, in the Colors: Explore Banyuwangi magazine article (pp. 96-104), there were 11 translation procedures found, namely: Adaptation, Amplification, Borrowing, Calque, Compensation, Generalization, Literal Translation, Modulation, Particularization, Reduction, and Transposition.